Interdependencies between Vitamin D-Binding Protein, Alpha-1 Antitrypsin and Neutrophil Proteins in Meconium of Full-term Neonates - Lisowska-Myjak, Barbara; Skarzynska, Ewa; Jakimiuk, Artur (Recent Developments in Chemistry and Biochemistry Research Vol. 11, 2025)
Background/Aims: Neutrophils are one of the hosts of innate immune cells detected at the maternal-fetal interface. Careful regulation of the inflammatory and immunoregulatory functions of these cells most likely plays a role in successful gestation. Still, neutrophil assays are not commonly used in perinatal diagnosis as there are no specific biological materials available for their detection that could be simply and noninvasively obtained from the intrauterine environment. Alpha-1 antitrypsin (AAT), vitamin-D binding protein (VDBP) and neutrophil granule proteins are specifically related to the neutrophil function and may be considered candidate biomarkers detected and measured in meconium (the first feces of newborn infants) as signals indicating abnormal processes in the fetal stage. Individual proteins found in meconium can be a source of information pertaining to the intrauterine metabolic processes. Methods: Concentrations of AAT, VDBP, calprotectin, myeloperoxidase, lactoferrin and elastase were measured using ELISA tests in 80 meconium samples collected from 19 healthy, full-term neonates. Results: The meconium concentrations of VDBP and AAT (mean± SD, [mg/g meconium]: 3.74±6.93, 3.72±1.79, respectively) were approximately 1000 times higher than those of the protein granule proteins calprotectin, myeloperoxidase, elastase and lactoferrin (mean± SD, [µg/g meconium]: 285.7±215.8, 1.83±1.73, 1.72±2.70, 45.58±78.89, respectively). The correlation between VDBP and AAT was negative (r= - 0.40. p=0.000) and those between VDBP and calprotectin (r=0.38, p=0.000) and VDBP and myeloperoxidase (r=0.45, p=0.000) were positive. AAT was found to correlate positively with lactoferrin (r=0.38, p=0.000). Conclusion: The correlations between the concentrations of VDBP and AAT, and with neutrophil granule proteins observed in meconium indicate their functional relationship in the intrauterine environment of the developing fetus. Meconium can be seen as an apparently underutilized source of biomarkers for the evaluation of metabolic processes specific to fetal development. The findings may offer new biomarkers for diagnosing abnormal intrauterine processes and help explore the metabolic conditions of the fetus. This research has potential implications in the field of neonatal diagnostics and fetal health monitoring.